All in all it’s just another branch in the tree: A new species of Acanthocercus Fitzinger, 1843 (Squamata: Agamidae), from Angola - Marques, Mariana P.; Parrinha, Diogo; Santos, Bruna S.; Bandeira, Suzana; Butler, Brett O.; Sousa, Ana Carolina A.; Bauer, Aaron M.; Wagner, Philipp (Zootaxa, 2022)
Recent integrative taxonomic studies of the agamid genus Acanthocercus Fitzinger, 1843 have shown that Angola harbors three different taxa, all within the Acanthocercus atricollis (Smith, 1849) species complex—A. cyanocephalus (Falk, 1925) in the northeastern parts of the country, A. margaritae Wagner et al. 2021 in the southern regions, and an unnamed species in the central and northwestern parts of Angola. Using the previously published molecular data as evidence of phylogenetic support and newly collected morphological, meristic and coloration data, we here describe this unnamed lineage as a new species. The new species is morphologically very similar to A. cyanocephalus, but it can easily be differentiated from the latter by the coloration pattern of displaying males, with a blue coloration restricted to the head region, and by its inferior scale counts compared to other species of the A. atricollis complex group. As reported in other studies in this group, male breeding coloration is an effective trait for diagnosing these morphologically conserved species. This description raises the number of Acanthocercus species recognized to 15 and is another contribution revealing the rich but still incompletely described herpetological diversity of Angola.